Parent–Teacher Partnerships and the Effectiveness of PAI Teaching Modules at MAN 1 Cianjur - Rudi Ahmad Suryadi; Ridha Nestu Adidarma; Uus Saripudin; Muhammad Murojab (UIN Sunan Gunung Djati Bandung, 2026)
This research is based on the urgency of building synergy between parents and teachers as a determining factor in the successful implementation of the Independent Curriculum, particularly in Islamic Religious Education (PAI) learning at MAN 1 Cianjur. The main objectives of this study are to describe the implementation of the PAI teaching module, assess the effectiveness of collaborative relationships between parents and teachers, and analyze the extent to which these interactions influence the successful implementation of the teaching module. The research uses a descriptive, quantitative approach by combining several data collection techniques, namely observation, interviews, documentation, and the distribution of questionnaires to students' teachers and parents as respondents. The research findings indicate that high-quality, intensive interactions between parents and teachers have a significant impact on the successful implementation of the PAI teaching module. Open two-way communication, parental involvement in the child's learning process, and consistent moral and spiritual support have been shown to increase students' motivation, discipline, and understanding of the subject matter. In addition, good collaboration also strengthens the integration of religious values in students' daily lives. In conclusion, the stronger and more effective the interaction between parents and teachers, the more optimal the implementation of Islamic Religious Education (PAI) teaching modules will be in achieving learning objectives aligned with the principles of the Independent Curriculum. Thus, this study emphasizes the importance of ongoing collaboration between schools and families as a key strategy in improving the quality of Islamic religious education at the madrasah level.